Embodied Knowledge Penghafal Al-Qur’an di Pondok Al-Qur’aniy, Surakarta - Rohman, Nur; Faizah, Jihan Billah (SUHUF, 2024)
This article discusses the embodied knowledge of Qur’an memorizers at tahfiz Islamic boarding schools in Indonesia. This research takes the locus at Pondok Pesantren Al-Qur’aniy as a representation of traditional Islamic boarding schools that deal with urban society and culture in Surakarta. Theoretically, this article seeks to see the practice of Qur’anic education and memorization as a form of bodily discipline within the framework of embodied knowledge, which is a way for someone to gain knowledge and articulate it in his practice. Through observations and interviews, this article argues that in the Qur’anic education and memorization process, some traditions remain a discipline and knowledge in their own right. Embodying knowledge is not only done through the absorption of static texts but also through dynamic texts. This knowledge is embodied in a person due to the discipline influenced by the culture and the surrounding agencies such as Kiai, family, teachers, and the people around him.